PENCEGAHAN STUNTING PADA ANAK DALAM PERSPEKTIF ISLAM DI KABUPATEN BATANG - Zahrotul Jannah; Zahirotul Wirda; Desy Adella; Nur Istiqomah; Muthmainnatun Mufidah; Muhtar Ali Ahmadi (PENDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a chronic health problem in children that can affect physical growth, cognitive and productivity in the future. This research aims to identify factors that cause stunting, evaluate effective prevention strategies, and analyze the role of government and society in overcoming it, especially in Batang Regency. Through the Participatory Action Research (PAR) approach, various prevention programs are implemented, such as education about the importance of balanced nutrition, environmental cleanliness, and child health care from an Islamic perspective. The results of this program show a significant reduction in the prevalence of stunting in Batang Regency, from 26.3% to 10.1% in 2023. This research concludes that collaboration between government, society and the application of Islamic values ​​can be an effective approach in preventing stunting . Keywords: stunting, health, society